Literature Review on Information Overload in the Period 1970 - 2017 (Journal of Universal Excellence, 2026)
Research Question (RQ): How has the Information overload literature evolved over the past five decades, which are its most important authors, and which organizational, business, and other factors have been highlighted as those that have had the greatest impact on information overload?Purpose: To inform the professional and general public why and how Information overload is created in companies and how it is understood by the management, owners and other stakeholders in these companies.Method: Comparative analysis of research on Information overload in the period 1970 - 2017 with emphasis on two conceptual research.Results: The research on Information overload should be further developed, as indicated by the low number of citations in the management literature. In terms of content, the discussions do not provide a sufficiently comprehensive picture of information overload, at the same time do not use interdisciplinary approaches, which would show the interconnections of different variables.Organization: The article will contribute to a greater understanding of management`s decision-making in an environment of uncertainty. From a practical point of view it the article is useful especially for private investors for improving their position in the agency relationship of corporate governance.Society: The article will contribute to a greater understanding of Information overload with the legislator, national regulators and other institutions which will enable owners and other stakeholders in companies a more equal role in corporate governance and thus greater efficiency and effectiveness of companies.Originality: The novelty is the unification of two different approaches in the analysis of the literature on Information overload - linear and functional, which provides an equivalent analysis of the literature throughout the period 1970 – 2017.Limitations/Future Research: The article is limited with conceptual research for the analysis of the literature on Information overload in the period 1970 - 2017. The content of the article opens up possibilities to shed light on the problem of Information overload in Slovenia and in general, taking into account need for a greater interdisciplinary approach.
Keywords: information asymmetry; information overload; information technology; management; shareholders